Demokratisasi Pendidikan Dalam Islam - Martina Martina; Fitri Sarinda; Dwi Noviani; Hilmin Hilmin (Concept: Journal of Social Humanities and Education, 2023)
Democratization in Islamic education is an approach that emphasizes democratic principles to achieve an inclusive and fair education system in accordance with Islamic teachings. This concept involves the active participation of all members of the educational community, ensuring inclusivity, and developing students' skills. In this abstract, we will explain the essence of the democratization of education in Islam and its impact on the development of a generation that has morals and makes positive contributions to society. The democratization of education in Islam includes the development of leadership skills and values. Islam teaches the values ​​of fair and responsible leadership. Therefore, a democratic education system in an Islamic context must pay special attention to the formation of students' character and leadership, so that they can contribute positively to society. Democratization of education in Islam is not just the implementation of the concept of democracy in educational practice, but also reflects Islamic values ​​that encourage justice, equality and active participation. By understanding and applying these principles, Islamic education can be a means of producing a generation that is not only academically intelligent, but also has noble character and is able to play an active role in building a just and harmonious society.